From Integrated Publication and Information Systems to Information and Knowledge Environments Essays Dedicated to Erich J. Neuhold on the Occasion of His 65th Birthday - Hemmje, Matthias.; Hemmje, Matthias.; Niederee, Claudia.; Niederee, Claudia.; Risse, Thomas.; Risse, Thomas. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2005)
This book constitutes a commemorative volume devoted to Erich J. Neuhold on the occasion of his 65th birthday. The 32 invited reviewed papers presented are written by students and colleagues of Erich Neuhold throughout all periods of his scientific career. The papers are organized in the following topical sections: Database management enabling information systems Semantic Web drivers for advanced information management Securing dynamic media content integration From digital libraries to intelligent knowledge environments Visualization – key to external cognition in virtual information environments From human-computer interaction to human-artefact interaction Domains for virtual information and knowledge environments.